Sex, human rights and AIDS: an analysis of new technologies for HIV prevention in the Brazilian context - Dulce Ferraz; Vera Paiva (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2015)
ABSTRACTWorldwide, HIV prevention is challenged to change because clinical trials show the protective effect of technologies such as circumcision, preexposure prophylaxis, and the suppression of viral load through antiretroviral treatment. In the face of demands for their implementation on population levels, the fear of stimulating risk compensation processes and of increasing riskier sexual practices has retarded their integration into prevention programs. In this article, following a narrative review of the literature on risk compensation using the PubMed database, we offer a critical reflection on the theme using a constructionist approach of social psychology integrated to the theoretical framework of vulnerability and human rights. The use of biomedical technologies for prevention does not consistently induce its users to the increase of riskier practices, and variations on the specificity of each method need to be carefully considered. Alternatives to the theories of sociocognitive studies, such as social constructionist approaches developed in the social sciences and humanities fields, indicate more comprehensive interpretations, valuing the notions of agency and rights. The critical analysis suggests priority actions to be taken in the implementation process: development of comprehensive programs, monitoring and fostering dialog on sexuality, and technical information. We highlight the need to implement a human rights-based approach and to prioritize dialog, stressing how complementary these technologies can be to meet different population needs. We conclude by stressing the need to prioritize sociopolitical changes to restore participation, dialog about sexuality, and emphasis on human rights such as core elements of the Brazilian AIDS policy.